Platelet LGALS3BP as a Mediator of Myeloid Inflammation in Systemic Lupus Erythematosus. Issue 5 (14th March 2023) - El Bannoudi, Hanane; Cornwell, MacIntosh; Luttrell‐Williams, Elliot; Engel, Alexis; Rolling, Christina; Barrett, Tessa J.; Izmirly, Peter; Belmont, H. Michael; Ruggles, Kelly; Clancy, Robert; Buyon, Jill; Berger, Jeffrey S.
Abstract : Objective: Platelets are mediators of inflammation with immune effector cell properties and have been implicated in the pathogenesis of systemic lupus erythematosus (SLE). This study investigated the role of platelet‐associated lectin, galactoside‐binding, soluble 3 binding protein (LGALS3BP) as a mediator of inflammation in SLE and as a potential biomarker associated with clinical phenotypes. Methods: We performed RNA sequencing on platelets from patients with SLE (n = 54) and on platelets from age‐, sex‐, and race/ethnicity‐matched healthy controls (n = 18) and measured LGALS3BP levels in platelet releasate and in circulating serum. We investigated the association between LGALS3BP levels and the prevalence, disease severity, and clinical phenotypes of SLE and studied platelet‐mediated effects on myeloid inflammation. Results: Platelets from patients with SLE exhibited increased expression of LGALS3BP (fold change 4.0, adjusted P  = 6.02 × 10 −11 ). Platelet‐released LGALS3BP levels were highly correlated with circulating LGALS3BP (R = 0.69, P  < 0.0001), and circulating LGALS3BP levels were correlated with the severity of disease according to the SLE Disease Activity Index (r = 0.32, P  = 0.0006). Specifically, circulating LGALS3BP levels were higher in SLE patients with lupus nephritis than in patients with inactive disease (4.0 μg/ml versus 2.3 μg/ml; P  < 0.001). Interferon‐α induced LGALS3BP transcription and translation in a megakaryoblastic cell line (MEG‐01) in a dose‐dependent manner. Recombinant LGALS3BP and platelet releasates from SLE patients enhanced proinflammatory cytokine production by macrophages. Conclusions: Our results support that platelets act as potent effector cells that contribute to the pathogenesis of SLE by secreting proinflammatory LGALS3BP, which also represents a novel biomarker of SLE clinical activity.